Technological scheme for lithium-substituted ferrite production under complex high-energy impact; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 474 - Lysenko E. N. Elena Nikolaevna; Nikolaev E. V. Evgeny Vladimirovich; Vlasov V. A. Vitaliy Anatolievich; Surzhikov A. P. Anatoly Petrovich (2020, 2020)
Title screen